A self-curing 3D printed magnesium oxychloride calcium sulfate composite bone cement scaffold, and a preparation method and application thereof

CN122520432BActive Publication Date: 2026-10-09NORTHERN JIANGSU PEOPLES HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611017869.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09
Estimated Expiration
2046-07-09

AI Technical Summary

Technical Problem

这极大限制了支架从单纯的“物理支撑”向“主动诱导骨再生”的智能型支架转化

Benefits of technology

1.本发明的支架打印后即可在常温条件下发生自固化反应,不需要传统的陶瓷高温烧结工艺,显著简化了制备流程,减少能耗,并为后续负载生物活性离子、小分子药物、蛋白、多肽或细胞因子提供了可能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122520432B_ABST
    Figure CN122520432B_ABST
Patent Text Reader

Abstract

The application discloses a self-curing 3D printing magnesium oxychloride calcium sulfate composite bone cement support and a preparation method and application thereof, and relates to the fields of biomedical materials and 3D printing technology. The preparation method comprises the following steps: preparing a liquid phase adjusting solution, preparing a composite printing liquid containing magnesium chloride, preparing a solid phase component, preparing a composite bone cement printing slurry, 3D printing a composite bone cement support, and a room temperature curing step. The prepared printing slurry has good shape retention performance, and after printing, no high-temperature sintering, photo-crosslinking, chemical crosslinking or other post-processing processes are needed, so that in-situ self-curing can be realized by means of a hydration and curing reaction of the magnesium oxychloride cement system, a three-dimensional porous support with high mechanical strength and a stable structure is formed, and the three-dimensional porous support can be widely applied to the fields of large bone defect repair, spinal fusion, bone graft replacement and other bone tissue engineering repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials and 3D printing technology, specifically relating to a self-curing 3D printed magnesium oxychloride / calcium sulfate composite bone cement scaffold that does not require high-temperature sintering, has high initial mechanical strength and good biodegradability, as well as its preparation method and application. Background Technology

[0002] Bone defects are common in clinical practice due to trauma, tumor resection, congenital malformations, and osteomyelitis. Currently, for the repair of large bone defects, materials with three-dimensional, regularly connected porous structures have become a research hotspot in bone tissue engineering because they can mimic the network structure of natural bone, providing the necessary space for cell adhesion, proliferation, blood vessel ingrowth, and the internal growth of new bone. With the development of computer-aided design and 3D printing technologies (such as extrusion 3D printing), it has become possible to create personalized and precise porous bone repair scaffolds based on imaging data of the patient's bone defect site.

[0003] However, existing 3D-printed bone repair scaffolds still face many intractable bottlenecks in practical fabrication and application: First, existing rigid bone repair scaffolds heavily rely on high-temperature sintering processes. Currently available or under-development ceramic bone scaffolds, such as hydroxyapatite, tricalcium phosphate, and bioactive glass, often exhibit extremely low green strength after printing. To achieve the mechanical strength required for implantation, they must be sintered for several hours in industrial furnaces at 1000°C or even higher. This high-temperature post-processing is not only cumbersome, energy-intensive, and time-consuming, but its most critical drawback is the inability to load any bioactive substances in situ. Heat-sensitive growth factors (such as BMP-2 and VEGF), proteins, active peptides, small-molecule clinical drugs, and even autologous cells will instantly denature and become inactive at high temperatures. This severely limits the transformation of scaffolds from simple "physical support" to intelligent scaffolds that "actively induce bone regeneration."

[0004] Secondly, traditional self-curing bone cement exhibits extremely poor rheological properties in 3D printing, making it difficult to balance continuous extrusion with shape retention. To avoid high-temperature sintering, researchers have attempted to directly use traditional self-curing bone cements (such as calcium phosphate cement (CPC) and acrylic ester cement (PMMA)) for 3D printing. However, these slurries face severe rheological discontinuities during the printing process. First, the curing reaction of the bone cement begins immediately after mixing, causing the slurry viscosity to increase exponentially over time. This easily clogs 20G micro-printing needles within minutes, making it impossible to achieve continuous and stable extrusion of large-size, complex structural scaffolds. Second, if the initial viscosity of the slurry is reduced to prevent clogging, the extruded slurry, lacking sufficient yield stress and interlayer stacking stability, will experience severe collapse and flow under gravity, leading to adjacent printed layers sticking together and micropores closing, making it impossible to accurately maintain the designed three-dimensional porous microstructure.

[0005] Third, existing self-curing materials lack sufficient resistance to disintegration and early strength after printing or in the early stages of implantation. Bone cement scaffold preforms printed at room temperature or low temperature are highly susceptible to "disintegration" (i.e., the uncured slurry components disperse and dissolve disorderly, leading to structural collapse) if they come into direct contact with body fluids, humid environments, or simulated body fluids before they are fully cured. Furthermore, existing room-temperature self-curing scaffolds generally have low early mechanical strength, making them unable to withstand localized mechanical loads in the early stages of implantation. This can easily lead to microscopic collapse, causing the pre-designed connecting channels to close and thus inhibiting vascular ingrowth.

[0006] Fourth, there is a severe mismatch between the in vivo degradation rate of the material and the rate of new bone regeneration. Single-component bone cements (such as pure magnesium-based cement or pure high-strength inorganic networks) often suffer from degradation that is either too fast or too slow. Excessive degradation can cause the material to lose its mechanical support before bone tissue has grown into it, and the locally released chemical ion concentration can be too high, leading to cytotoxicity or aseptic inflammation. Conversely, excessively slow degradation (such as non-degradable PMMA or some special cements that degrade extremely slowly) can cause the material to occupy space for a long time, forming a foreign body in the body and hindering the complete regeneration and remodeling of new bone.

[0007] Therefore, how to develop a composite bone cement scaffold that possesses excellent shear-thinning 3D printing rheological properties, high shape retention, strong disintegration resistance, and can self-cur at room temperature without high-temperature sintering, while also having high early mechanical strength and excellent in vivo degradability is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0008] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a self-curing 3D-printed magnesium oxychloride calcium sulfate composite bone cement scaffold, its preparation method, and its applications. This scaffold can be prepared at room temperature without high-temperature sintering, possesses high initial mechanical strength, a stable porous structure, and biodegradability. The invention features a simple preparation process, high molding efficiency, and requires no additional curing treatment. It is suitable for the rapid construction of personalized bone repair implants and can be widely applied in the repair of large bone defects, spinal fusion, bone graft replacement, and other bone tissue engineering repair fields.

[0009] As a first aspect of the present invention, the present invention provides a method for preparing a self-curing 3D printed magnesium oxychloride calcium sulfate composite bone cement scaffold, comprising the following steps: (1) Preparation of liquid phase conditioning solution: Weigh carboxylated cellulose nanofibers and xanthan gum, add them to deionized water, and make the carboxylated cellulose nanofibers fully dispersed and the xanthan gum fully dissolved to obtain a homogeneous and stable liquid phase conditioning solution, wherein the mass fraction of carboxylated cellulose nanofibers is 4-10 wt% and the mass fraction of xanthan gum is 0.6-1.5 wt%; (2) Prepare a composite printing solution containing magnesium chloride: Weigh magnesium chloride hexahydrate at a ratio of 0.4-0.7 g / ml, add it to the liquid phase conditioning solution obtained in step (1), and continue stirring until the magnesium chloride hexahydrate is completely dissolved to obtain a composite printing solution containing magnesium chloride. (3) Preparation of solid phase component: Weigh heavy magnesium oxide powder and hemihydrate calcium sulfate powder, and mix them thoroughly at a mass ratio of 0.3-0.8:0.2-0.7 to obtain magnesium-calcium composite solid phase component; (4) Preparation of composite bone cement printing slurry: The magnesium-calcium composite solid phase component obtained in step (3) is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.0-1.5 g / mL to obtain composite bone cement printing slurry; (5) 3D printing composite bone cement scaffold: The composite bone cement printing slurry prepared in step (4) is loaded into the 3D printing cylinder, the printing parameters are set, and the composite bone cement printing slurry is printed into a three-dimensional composite bone cement scaffold blank. (6) Room temperature curing: The preform of the printed composite bone cement scaffold is placed in a room temperature air environment for static curing.

[0010] Preferably, in step (1), magnetic stirring is performed at 37°C to fully disperse the carboxylated cellulose nanofibers and fully dissolve the xanthan gum, resulting in a uniform and stable liquid phase conditioning solution.

[0011] Preferably, in step (3), magnesium oxide powder and hemihydrated calcium sulfate powder are placed in a three-dimensional mixer and mixed thoroughly for 6 hours to obtain a uniform magnesium-calcium composite solid phase component.

[0012] Preferably, in step (4), the magnesium-calcium composite solid phase component is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.2 g / mL to obtain composite bone cement printing slurry.

[0013] Preferably, in step (5), the printing parameters include printing path, number of printing layers, line spacing, layer height, nozzle diameter, and extrusion speed.

[0014] Preferably, in step (5), the three-dimensional structure includes cylindrical, cuboid, grid-like, and irregular scaffold structures that match the morphology of bone defects.

[0015] Preferably, in step (6), the solidification is allowed to proceed for 60-480 min.

[0016] As a second aspect of the present invention, the present invention provides a magnesium oxychloride calcium sulfate composite bone cement scaffold prepared by the above method.

[0017] Preferably, the porosity of the magnesium oxychloride calcium sulfate composite bone cement scaffold is 20% to 60%, and the compressive strength is 30 to 70 MPa.

[0018] As a third aspect of the present invention, the present invention provides the application of the above-mentioned magnesium oxychloride calcium sulfate composite bone cement scaffold in the preparation of bone defect repair materials.

[0019] The beneficial effects of this invention are: 1. The scaffold of the present invention can undergo a self-curing reaction at room temperature after printing, without the need for traditional high-temperature ceramic sintering process, which significantly simplifies the preparation process, reduces energy consumption, and provides the possibility for subsequent loading of bioactive ions, small molecule drugs, proteins, peptides or cytokines.

[0020] 2. In this invention, magnesium oxychloride cement phase is used as the core solidification phase of the scaffold, providing excellent early mechanical support; hemihydrated calcium sulfate assists in early solidification, improving initial stability and anti-disintegration performance; carboxylated cellulose nanofibers form a fiber reinforcement network inside, giving the scaffold excellent crack resistance and toughness.

[0021] 3. This invention uses a combination of xanthan gum and carboxylated cellulose nanofibers, which significantly improves the shear thinning behavior of the slurry and the interlayer stacking stability, ensuring continuous and smooth extrusion and high shape retention during the printing process.

[0022] 4. The calcium sulfate phase in the composite network of this invention has good biocompatibility, osteoconductivity and in vivo degradability. After implantation, it gradually degrades, which can release space for cell migration, blood vessel ingrowth and new bone formation, and effectively regulate the overall degradation rate of the scaffold. Attached Figure Description

[0023] Figure 1 This is a photograph of the actual slurry extrusion test conducted on the printing nozzle in Example 1. Figure 2 Three-dimensional scaffold morphology images of different shapes printed in Example 1; Figure 3 The image shows the X-ray diffraction (XRD) pattern of the scaffold after curing in Example 1. Figure 4 This is an in vitro degradation curve of heavy magnesium oxide and calcium sulfate at different mass ratios in Example 3; Figure 5 This is a schematic diagram of the cell proliferation experiment results after the scaffold solidification in Example 4; Figure 6 Microscopic images of calcium nodules after intervention with osteogenic induction culture medium prepared from the scaffold extract in Example 5 on BMSCs; Figure 7 This is a schematic diagram of the quantitative analysis results of calcium deposition in Example 5. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention in any way. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. It should also be understood that the terminology used in the embodiments of this invention is for describing specific implementation schemes and not for limiting the scope of protection of this invention.

[0025] When a range of values ​​is given, it should be understood that, unless otherwise stated in this invention, the two endpoints of each range and any value between the two endpoints may be selected.

[0026] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly used in the field to which this invention pertains. The terminology used to describe this invention is intended only to describe a particular implementation and is not intended to limit the scope of the teachings. This invention can be implemented using any prior art methods, apparatus, and materials similar to or equivalent to those described, used, or made in the embodiments of this invention.

[0027] The term “and / or” as used herein should be understood to mean any one of the options or any combination of two or more of the options.

[0028] As used herein, the term "about" indicates a range of ±20% of the following value. In some embodiments, the term "about" indicates a range of ±10% of the following value. In some embodiments, the term "about" indicates a range of ±5% of the following value.

[0029] This invention provides a method for preparing a self-curing 3D-printed magnesium oxychloride calcium sulfate composite bone cement scaffold, comprising the following steps: (1) Preparation of liquid phase conditioning solution: Weigh carboxylated cellulose nanofibers and xanthan gum, add them to deionized water, so that the carboxylated cellulose nanofibers are fully dispersed and the xanthan gum is fully dissolved, so as to obtain a uniform and stable liquid phase conditioning solution. The mass fraction of carboxylated cellulose nanofibers is 4-10 wt%, and the mass fraction of xanthan gum is 0.6-1.5 wt%.

[0030] In a preferred embodiment, the carboxylated cellulose nanofibers have a mass fraction of 5 wt% and the xanthan gum has a mass fraction of 1 wt%.

[0031] Carboxylated cellulose nanofibers and xanthan gum, rheology modifiers, are dissolved or dispersed in a liquid to form a liquid-phase system with viscosity and shear thinning properties. This liquid-phase system can impart good extrudability to the slurry and can also participate in or regulate the hydration, self-curing, or ionic crosslinking reactions of bone cement.

[0032] In a preferred embodiment, magnetic stirring is performed at 37°C to fully disperse the carboxylated cellulose nanofibers and fully dissolve the xanthan gum, resulting in a homogeneous and stable liquid conditioning solution.

[0033] The liquid phase conditioning fluid has a certain viscosity and excellent shear thinning properties. Under shearing action, the viscosity decreases, which is beneficial for the continuous extrusion of slurry from the printing needle or nozzle during the subsequent 3D printing process.

[0034] (2) Preparation of composite printing solution containing magnesium chloride: Weigh magnesium chloride hexahydrate at a ratio of 0.4-0.7 g / ml, add it to the liquid phase conditioning solution obtained in step (1), and continue stirring until magnesium chloride hexahydrate is completely dissolved to obtain composite printing solution containing magnesium chloride.

[0035] The composite printing fluid can impart good extrudability, shear thinning and printing shape retention to bone cement slurry through carboxylated cellulose nanofibers and xanthan gum. On the other hand, the magnesium chloride hexahydrate in the composite printing fluid can provide magnesium salt and chloride ion environment for the subsequent hydration of heavy magnesium oxide and magnesium oxychloride cementing reaction, thereby regulating the hydration and self-curing process of the slurry.

[0036] (3) Preparation of solid phase component: Weigh heavy magnesium oxide powder and hemihydrate calcium sulfate powder, mix them thoroughly at a mass ratio of 0.3-0.8:0.2-0.7 to obtain magnesium-calcium composite solid phase component.

[0037] In a preferred embodiment, magnesium oxide powder and hemihydrated calcium sulfate powder are placed in a three-dimensional mixer and mixed thoroughly for 6 hours to obtain a uniform magnesium-calcium composite solid phase component.

[0038] In a preferred embodiment, the mass ratio of heavy magnesium oxide powder to hemihydrate calcium sulfate powder is 1:1.

[0039] Heavy magnesium oxide, as the main alkaline reaction component, undergoes hydration and magnesium oxychloride cementation reactions in an aqueous environment containing magnesium chloride, forming the magnesium oxychloride cement solidified phase, which is the main load-bearing component in the early stage of the scaffold. Hemihydrated calcium sulfate, as a hydrated and degradable calcium-based inorganic component, further hydrates in an aqueous environment or after implantation to form calcium sulfate dihydrate crystals, which together with the magnesium oxychloride cement solidified phase to construct a composite inorganic support network.

[0040] (4) Preparation of composite bone cement printing slurry: The magnesium-calcium composite solid phase component obtained in step (3) is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.0-1.5 g / mL to obtain composite bone cement printing slurry; As a preferred embodiment, the magnesium-calcium composite solid phase component is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.2 g / mL to obtain composite bone cement printing slurry.

[0041] The liquid phase component is slowly added to the solid phase and thoroughly mixed using a scraper to ensure uniform contact between the solid and liquid phases, resulting in a homogeneous, fine composite bone cement printing slurry without significant agglomeration.

[0042] The resulting composite bone cement printing slurry exhibits excellent extrudability, stackability, shape retention, and self-curing properties, making it suitable for 3D printing. During printing, the slurry can smoothly pass through the printing needle or nozzle under shearing action, and after extrusion, it quickly recovers its viscosity and maintains the morphology of the printed filaments, thus achieving layer-by-layer stacking.

[0043] (5) 3D printing composite bone cement scaffold: The composite bone cement printing slurry prepared in step (4) is loaded into the 3D printing cylinder, the printing parameters are set, and the composite bone cement printing slurry is printed into a three-dimensional composite bone cement scaffold blank.

[0044] The scaffold model is obtained through computer-aided design and extruded layer by layer according to the set path. By adjusting the printing parameters, controllable preparation within the porosity range of 20% to 60% can be achieved. The compressive strength of the scaffold after curing can reach 30 to 70 MPa, which has both excellent mechanical support performance and structural stability.

[0045] (6) Room temperature curing: The preform of the printed composite bone cement scaffold is placed in a room temperature air environment for static curing.

[0046] As a preferred embodiment, the curing time is 60-480 min.

[0047] After printing, the heavy magnesium oxide, magnesium chloride hexahydrate, and water in the slurry undergo a hydration and self-curing reaction to form a magnesium oxychloride cement solidified phase; at the same time, hemihydrate calcium sulfate further participates in the hydration reaction, jointly improving the structural stability and early mechanical support performance of the printed support.

[0048] The present invention also provides the application of the above-mentioned composite bone cement scaffold in the preparation of bone defect repair materials.

[0049] The following embodiments and accompanying drawings are provided to aid in understanding the present invention. However, it should be understood that these embodiments are for illustrative purposes only and do not constitute any limitation. The actual scope of protection of the present invention is set forth in the claims. It should be understood that any modifications and changes can be made without departing from the spirit of the present invention. Unless otherwise specified, the raw materials used in the embodiments are all commercially available products in the art, their specifications are conventional specifications in the art, and the methods used are conventional methods in the art. The instruments and equipment used in the embodiments are conventional instruments and equipment in the art.

[0050] Example 1 This embodiment provides a method for preparing a self-curing 3D printed magnesium oxychloride and calcium sulfate composite bone cement scaffold, including the following steps: (1) Preparation of liquid phase conditioning solution Carboxylated cellulose nanofibers and xanthan gum were weighed and added to deionized water to make the mass fraction of carboxylated cellulose nanofibers 5 wt% and the mass fraction of xanthan gum 1 wt%. The mixture was magnetically stirred at 37°C to fully disperse the carboxylated cellulose nanofibers and fully dissolve the xanthan gum, resulting in a homogeneous and stable liquid conditioning solution.

[0051] (2) Prepare a composite printing solution containing magnesium chloride. Weigh 0.564 g / ml magnesium chloride hexahydrate and add it to the rheology conditioning solution obtained in step (1). Continue stirring until the magnesium chloride hexahydrate is completely dissolved to obtain a composite printing solution containing magnesium chloride.

[0052] (3) Preparation of solid components Weigh out heavy magnesium oxide powder and hemihydrate calcium sulfate powder, and mix them at a mass ratio of 1:1. Place the two in a three-dimensional mixer and mix thoroughly for 6 hours to obtain a homogeneous magnesium-calcium composite solid phase.

[0053] (4) Preparation of composite bone cement printing slurry The magnesium-calcium composite solid phase component obtained in step (3) was added to the composite printing liquid containing magnesium chloride obtained in step (2) at a solid-liquid ratio of 1.2 g / mL. The solid-liquid ratio is the ratio of the mass of the solid phase component to the volume of the composite printing liquid.

[0054] (5) 3D printed bracket blank The prepared composite bone cement printing slurry was loaded into a 3D printing cylinder, and a pre-set 3D model was imported into the computer-aided design system. The model dimensions were: length 10.00 mm, width 10.00 mm, and height 10.00 mm. The 3D printing parameters were set as follows: printing needle specification: 20G, printing speed: 5.00 mm / s, extrusion speed: 5 mm³ / s, layer height: 0.25 mm, and path spacing: 3.00 mm. Figure 1 As shown, extrusion tests were conducted using a printing nozzle. The results showed that the slurry could be continuously and uniformly extruded from the nozzle, without any obvious nozzle blockage, filament breakage, or phase separation during the extrusion process. The extruded slurry filaments exhibited good shape retention and could be stacked layer by layer according to a preset path to form a three-dimensional scaffold preform with a regular porous structure.

[0055] like Figure 2 As shown, by adjusting printing parameters such as the printing path, number of printing layers, line spacing, layer height, nozzle diameter, and extrusion speed, the composite bone cement printing slurry can be printed into various three-dimensional structures, including cylindrical, cuboid, mesh-like, and irregular scaffold structures that match the morphology of bone defects. Furthermore, by changing the printing line spacing and layer height, the pore structure of the scaffold can be controllably constructed. When the printing line spacing increases, the gap between adjacent slurry filaments increases, and the pore size of the resulting scaffold increases accordingly; when the printing line spacing decreases, the gap between adjacent slurry filaments decreases, and the pore size of the resulting scaffold decreases accordingly.

[0056] (6) Room temperature curing The printed preform was left to cure in room temperature air for 240 minutes. The results showed that the printed preform could self-cure through internal hydration reactions without the need for high-temperature sintering or additional chemical cross-linking. After curing, the preform maintained the overall shape and pore structure of the printed design, without significant collapse, flow, or structural deformation.

[0057] like Figure 3As shown, XRD analysis revealed that the final product obtained was Mg3(OH)5Cl·4H2O, forming a dense magnesium oxychloride hydration network dominated by five phases in situ. This facilitated rapid self-curing and provided crucial mechanical support and structural stability in the early stages. In the moist ionic environment within the implant, the hemihydrated calcium sulfate (CaSO4·0.5H2O) introduced into the system further underwent continuous hydration to generate dihydrate calcium sulfate (CaSO4·2H2O) crystals. These crystals gradually precipitated, filled, and bridged the pores between the original magnesium oxychloride gel framework, jointly constructing a multi-scale interpenetrating composite inorganic support network with the magnesium oxychloride hydration products.

[0058] This dynamic synergistic curing process realizes a mechanical evolution mechanism of "rapid initial setting - continuous enhancement": on the one hand, it avoids the strength reduction problem caused by structural rearrangement after the early hydration of traditional magnesium oxychloride bone cement; on the other hand, it strengthens and densifies the microstructure through the later growth of calcium sulfate crystals, thereby significantly improving the overall compressive strength retention rate and long-term structural stability, making it more suitable for load-bearing bone defect repair applications.

[0059] Example 2 This embodiment investigates the effect of printing line spacing on the mechanical properties and pore structure of the magnesium oxychloride-based composite bone cement scaffold. The printable bone cement slurry prepared in Example 1 is used as the printing material. While keeping the nozzle diameter, layer height, printing speed, extrusion pressure and curing conditions consistent, only the line spacing between adjacent printing filaments is changed to prepare three-dimensional porous scaffolds with different pore structures.

[0060] Specifically, the printable bone cement slurry was loaded into a printing cylinder and stacked layer by layer through 3D printing, with different printing line spacings, such as 2 mm, 2.4 mm, 2.8 mm, and 3.2 mm. After printing, the resulting scaffold blank was placed in room temperature air for self-curing, causing the heavy magnesium oxide, magnesium chloride, and water to undergo a magnesium oxychloride cementation reaction, forming a magnesium oxychloride cement solidified phase mainly composed of Mg3(OH)5Cl·4H2O; simultaneously, hemihydrated calcium sulfate participated as an auxiliary inorganic phase in the construction of the scaffold structure. After curing, the porosity and compressive mechanical properties of scaffolds with different line spacings were tested, and the results are shown in Table 1.

[0061] Table 1

[0062] The results above show that adjusting the printing line spacing can effectively regulate the scaffold porosity and mechanical properties. When the line spacing is too small, the scaffold porosity is insufficient; when the line spacing is too large, the scaffold's mechanical strength decreases significantly. Considering the dual requirements of early mechanical support and tissue ingrowth space for the bone repair scaffold, a line spacing of approximately 2.8 mm is preferred. At this distance, the scaffold compressive strength is approximately 30 MPa, and the porosity is approximately 60%, which represents the optimal printing parameters for this invention.

[0063] Example 3 This embodiment is used to evaluate the effect of different ratios of heavy magnesium oxide to hemihydrated calcium sulfate on the degradation performance of 3D printed composite bone cement scaffolds.

[0064] This embodiment investigates the effect of the mass ratio of heavy magnesium oxide to hemihydrated calcium sulfate in the solid phase on the degradation performance of the magnesium oxychloride-based composite bone cement scaffold. The liquid phase system described in Example 1 is used as the composite printing liquid. While keeping the liquid phase composition, solid-liquid ratio, nozzle diameter, layer height, printing speed, extrusion pressure, printing line spacing and curing conditions consistent, only the mass ratio of heavy magnesium oxide to hemihydrated calcium sulfate in the solid phase is changed to prepare three-dimensional porous scaffolds with different degradation performance.

[0065] like Figure 4 As shown, heavy magnesium oxide and hemihydrated calcium sulfate were weighed and thoroughly mixed at mass ratios of 1:0, 0.8:0.2, 0.5:0.5, and 0.3:0.7, respectively, to obtain solid powders with different compositions. Subsequently, these solid powders were mixed with liquid systems containing magnesium chloride, carboxylated cellulose nanofibers, and xanthan gum to obtain printable bone cement slurry with extrudability and self-support. The resulting slurry was loaded into a 3D printing cylinder and printed layer by layer to prepare a three-dimensional porous scaffold with a regular pore structure. After printing, the resulting scaffold blank was placed in room temperature air for self-curing, causing the heavy magnesium oxide, magnesium chloride, and water to undergo a magnesium oxychloride cementation reaction, forming a magnesium oxychloride cement solidified phase mainly composed of Mg3(OH)5Cl·4H2O; simultaneously, hemihydrated calcium sulfate gradually hydrated in an aqueous environment to form calcium sulfate dihydrate crystals, jointly constructing a composite inorganic support network.

[0066] To evaluate the degradation performance of scaffolds with different component ratios, the initial dry weight W0 was recorded. Subsequently, each group of scaffolds was immersed in phosphate buffer at 37 °C for in vitro degradation experiments. At least three parallel samples were prepared for each group, and samples were removed at predetermined time points, gently rinsed with deionized water, and dried to constant weight. The dry weight Wt after degradation was recorded, and the mass loss rate was calculated using the following formula: Quality loss rate (%) = (W0 - Wt) / W0 × 100% The results showed that scaffolds with different mass ratios of heavy magnesium oxide to calcium sulfate hemihydrate all exhibited certain in vitro degradation behavior, but the degradation rates differed significantly. Among them, the scaffold with a mass ratio of 1:0 of ​​heavy magnesium oxide to calcium sulfate hemihydrate did not contain calcium sulfate hemihydrate, and its main solidified phase was magnesium oxychloride cement phase. This scaffold had a relatively dense structure, the slowest degradation rate, and the lowest mass loss rate after immersion. This indicates that although the single magnesium oxychloride cement system has good structural stability, its degradation is relatively slow.

[0067] When the mass ratio of heavy magnesium oxide to calcium sulfate hemihydrate was adjusted to 0.8:0.2, a certain amount of calcium sulfate hemihydrate was introduced into the scaffold. During the curing and soaking process, the calcium sulfate hemihydrate hydrated to form calcium sulfate dihydrate, which gradually dissolved in the aqueous environment, resulting in a higher scaffold mass loss rate compared to the 1:0 group. This indicates that the introduction of calcium sulfate hemihydrate can improve the problem of slow degradation of magnesium oxychloride-based bone cement scaffolds.

[0068] When the mass ratio of heavy magnesium oxide to hemihydrate calcium sulfate is 0.5:0.5, the proportion of the magnesium oxychloride cement-cured phase and the degradable calcium sulfate phase in the scaffold is relatively moderate. Simultaneously, it exhibits a relatively gradual and significant mass loss behavior during immersion, indicating that this ratio achieves a good balance between structural stability and degradability.

[0069] When the mass ratio of heavy magnesium oxide to hemihydrated calcium sulfate was 0.3:0.7, the proportion of hemihydrated calcium sulfate in the scaffold further increased, the dissolution effect of the dihydrate calcium sulfate phase during degradation became more pronounced, the scaffold mass loss rate further increased, and the degradation rate was faster. This result indicates that as the hemihydrated calcium sulfate content increases, the scaffold's degradation performance is enhanced; however, an excessively high proportion of calcium sulfate phase may lead to accelerated scaffold degradation, thereby affecting its structural maintenance ability in the early stages of bone defect repair.

[0070] In summary, the in vitro degradation rate of the magnesium oxychloride-based composite bone cement scaffold gradually increased with the increase of the proportion of hemihydrated calcium sulfate in the solid phase component. This indicates that the present invention can effectively regulate the degradation performance of the 3D-printed composite bone cement scaffold by controlling the mass ratio of heavy magnesium oxide to hemihydrated calcium sulfate, thereby meeting the needs for early support and later degradation replacement in different bone defect repair scenarios. Experimental results show that the mass of the composite bone cement scaffold prepared by the present invention gradually decreased with the extension of soaking time, indicating that the scaffold has sustainable degradation capability in an aqueous environment. In the early stage of degradation, the overall morphology and 3D-printed pore structure of the scaffold remained intact, indicating that it can maintain the necessary mechanical support and spatial structure in the early stage of bone defect repair. With further extension of soaking time, micropores, roughening, and local dissolution phenomena gradually appeared on the scaffold surface, and the pore connectivity was further enhanced, which is conducive to cell adhesion, blood vessel ingrowth, and the crawling replacement of new bone tissue.

[0071] Example 4 This embodiment is used to evaluate the in vitro biocompatibility of the 3D printable self-curing magnesium oxychloride / calcium sulfate composite bone cement scaffold prepared in Example 1.

[0072] Composite bone cement printing slurry was prepared according to the method described in Example 1, and a porous scaffold preform was obtained by 3D printing. The printed scaffold was placed in a room temperature air environment for self-curing. After it was fully cured, a magnesium oxychloride / calcium sulfate composite bone cement scaffold sample was obtained. Subsequently, the scaffold sample was subjected to ultraviolet irradiation, sterile PBS washing, or ethylene oxide sterilization before use.

[0073] The sterilized scaffold samples were added to complete culture medium at a mass-to-volume ratio of 0.2 g / mL and extracted at 37℃ and 5% CO2 for 24 h to obtain the material extract. After extraction, the extract was filtered through a sterile filter membrane and used as the culture medium for the experimental group.

[0074] Bone marrow mesenchymal stem cells (BMSCs) were selected as evaluation cells. BMSCs were processed at a ratio of 2 × 10⁻⁶ cells / year. 3 Cells were seeded at a density of [number] cells / well in 96-well plates and cultured in complete culture medium. After cell attachment, the original culture medium was discarded, and 100 μL of the above-mentioned composite bone cement scaffold extract was added for further culture. Cell proliferation activity was assessed using the CCK-8 assay (using a 1:9 ratio of CCK extract) at 1, 3, and 5 days of culture. 8. Prepare by mixing reagents and complete culture medium.

[0075] A control group was also set up, using 2×10⁶ wells in a 96-well plate. 3 BMSCs were seeded at a density of / wells, and after the cells were fully adhered, they were cultured for 1, 3, and 5 days. At the corresponding culture time points, the cell proliferation activity was detected using CCK8 working solution, and the final values ​​were read using an ELISA reader.

[0076] like Figure 5 As shown, compared with the blank culture medium control group, the extract of the present invention (experimental group) significantly promoted the proliferation of BMSCs on days 1, 3, and 5 of culture. This excellent performance, exceeding the conventional "non-toxic" standard, may be related to the following factors: (1) No organic solvents, highly toxic crosslinking agents or antibiotics are introduced into the material system. After printing, the self-curing is mainly achieved through inorganic hydration reaction, which reduces the risk of potential toxic residues. (2) The magnesium oxychloride bone cement solidified phase formed by the reaction of heavy magnesium oxide, magnesium chloride hexahydrate and water provides a stable structure for the scaffold, and at the same time, the material can release an appropriate amount of Mg during the extraction process. 2+ This helps maintain the ion microenvironment required for cell growth; (3) Hemihydrated calcium sulfate further hydrates in an aqueous environment to form dihydrate calcium sulfate, and can release Ca. 2+ This helps to provide a favorable calcium ion environment for BMSCs proliferation and subsequent osteogenic differentiation; (4) The porous scaffold structure formed by 3D printing has good pore connectivity, which can provide a spatial basis for cell migration, adhesion, proliferation and subsequent tissue ingrowth.

[0077] The above results indicate that the 3D printable self-curing magnesium-calcium composite bone cement scaffold prepared in this embodiment not only has no obvious cytotoxicity, but also provides a suitable microenvironment for the survival and proliferation of BMSCs, demonstrating its good biocompatibility and application potential as a bone defect repair scaffold material.

[0078] Example 5 This embodiment is used to evaluate the effect of the 3D printable self-curing magnesium oxychloride / calcium sulfate composite bone cement scaffold prepared in Example 1 on osteogenic differentiation and mineralization capacity of bone marrow mesenchymal stem cells (BMSCs).

[0079] Composite bone cement printing slurry was prepared according to the method described in Example 1, and a porous scaffold preform was obtained by 3D printing. The printed scaffold was placed in a room temperature air environment for full self-curing to obtain magnesium oxychloride / calcium sulfate composite bone cement scaffold samples. Subsequently, the scaffold samples were subjected to ultraviolet irradiation, sterile PBS washing, or ethylene oxide sterilization before use.

[0080] The sterilized scaffold samples were added to complete culture medium or osteogenic induction culture medium at a mass-to-volume ratio of 0.2 g / mL and extracted at 37℃ and 5% CO2 for 24 h to obtain the material extract. After extraction, the extract was filtered through a sterile filter membrane and used as the culture medium for the experimental group.

[0081] BMSCs were selected as evaluation cells. BMSCs were seeded in 24-well plates. After cell attachment, the original culture medium was discarded, and the above-mentioned composite bone cement scaffold extract was added for further culture. BMSCs cultured in ordinary osteogenic induction medium served as a control group. Alizarin Red S (ARS) staining and quantitative analysis were performed on day 14 to evaluate the effect of the material on the osteogenic capacity of BMSCs.

[0082] (1) ARS staining and quantitative analysis of mineralized nodules After 14 days of culture, the culture medium was discarded, and the cells were gently washed with PBS. Cells were then fixed with 4% paraformaldehyde, followed by washing with PBS. Alizarin Red staining solution was added for incubation, allowing the cells to bind with calcium salts deposited in the extracellular matrix. After staining, the cells were thoroughly washed with deionized water to remove unbound dye, and the formation of mineralized nodules was observed under an inverted microscope.

[0083] To further perform quantitative analysis, alizarin red dye bound to perchloric acid was added, and the absorbance was then measured at 420 nm using an ELISA reader to evaluate the extracellular calcium salt deposition levels in different groups.

[0084] like Figure 6-7 As shown, ARS staining results indicated that with prolonged culture time, all groups of cells formed a certain degree of mineralization deposition, but the experimental group formed more, larger, and darker red mineralized nodules. ARS quantitative analysis showed that the calcium salt deposition level in the experimental group was higher than that in the control group, indicating that the magnesium oxychloride / calcium sulfate composite bone cement scaffold prepared in this embodiment can further promote BMSCs mineralization and extracellular matrix calcification.

[0085] Further analysis suggests that the material's role in promoting osteogenic differentiation and mineralization deposition is mainly related to the following factors: The 3D-printable, self-curing magnesium oxychloride / calcium sulfate composite bone cement scaffold prepared in this embodiment promotes osteogenic differentiation and mineralization deposition of bone mesenchymal stem cells (BMSCs). This effect is mainly attributed to the Mg2+ formed during the extraction and degradation of the material. 2+ / Ca 2+ It is related to the synergistic ion microenvironment.

[0086] First, heavy magnesium oxide forms a magnesium oxychloride cement-based solidified phase in an aqueous environment containing magnesium chloride. This solidified phase maintains the early mechanical support and structural stability of the scaffold while gradually releasing appropriate amounts of Mg in body fluids or culture media. 2+ Mg 2+ It is one of the important inorganic ions in bone tissue metabolism and bone repair, and can participate in cell adhesion, cytoskeleton remodeling, energy metabolism, and osteogenic-related signal regulation. Appropriate amounts of Mg... 2+ This promotes the adhesion and spread of BMSCs and further enhances their ability to differentiate into osteoblasts. Secondly, hemihydrated calcium sulfate further hydrates in an aqueous environment to form dihydrate calcium sulfate crystals, and continuously releases Ca during the material degradation process. 2+ Ca 2+ It is an important ionic basis for bone matrix mineralization and can participate in the deposition of extracellular matrix calcium salts and the formation of mineralized nodules. Appropriate amounts of Ca... 2+ It can provide the necessary inorganic ion source for matrix mineralization in the later stage of osteogenic differentiation of BMSCs and is conducive to extracellular calcium salt deposition. Therefore, in ARS staining, it is manifested as an increase in the number of mineralized nodules, an expansion of the staining area and an enhanced degree of calcification.

[0087] Therefore, the enhanced ARS staining and quantitative results indicate that the scaffold can further promote the formation of mineralized nodules in BMSCs. These results demonstrate that the material of this invention, through Mg... 2+ / Ca 2+Synergistic release creates a bone ion microenvironment, thereby endowing the scaffold with good osteogenic activity and potential for bone defect repair.

[0088] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the appended claims.

Claims

1. A method for preparing a self-curing 3D-printed magnesium oxychloride calcium sulfate composite bone cement scaffold, characterized in that, Includes the following steps: (1) Preparation of liquid phase conditioning solution: Weigh carboxylated cellulose nanofibers and xanthan gum, add them to deionized water, and make the carboxylated cellulose nanofibers fully dispersed and the xanthan gum fully dissolved to obtain a homogeneous and stable liquid phase conditioning solution, wherein the mass fraction of carboxylated cellulose nanofibers is 4-10 wt% and the mass fraction of xanthan gum is 0.6-1.5 wt%; (2) Prepare a composite printing solution containing magnesium chloride: Weigh magnesium chloride hexahydrate at a ratio of 0.4-0.7 g / ml, add it to the liquid phase conditioning solution obtained in step (1), and continue stirring until the magnesium chloride hexahydrate is completely dissolved to obtain a composite printing solution containing magnesium chloride. (3) Preparation of solid phase component: Weigh heavy magnesium oxide powder and hemihydrate calcium sulfate powder, and mix them thoroughly at a mass ratio of 0.3-0.8:0.2-0.7 to obtain magnesium-calcium composite solid phase component; (4) Preparation of composite bone cement printing slurry: The magnesium-calcium composite solid phase component obtained in step (3) is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.0-1.5 g / mL to obtain composite bone cement printing slurry; (5) 3D printing composite bone cement scaffold: The composite bone cement printing slurry prepared in step (4) is loaded into the 3D printing cylinder, the printing parameters are set, and the composite bone cement printing slurry is printed into a three-dimensional composite bone cement scaffold blank. (6) Room temperature curing: The preform of the printed composite bone cement scaffold is placed in a room temperature air environment for static curing.

2. The method for preparing a self-curing 3D printed magnesium oxychloride calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (1), magnetic stirring is performed at 37°C to fully disperse the carboxylated cellulose nanofibers and fully dissolve the xanthan gum, resulting in a uniform and stable liquid phase conditioning solution.

3. The method for preparing a self-curing 3D printed magnesium oxychloride and calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (3), magnesium oxide powder and hemihydrated calcium sulfate powder are placed in a three-dimensional mixer and mixed thoroughly for 6 hours to obtain a uniform magnesium-calcium composite solid phase component.

4. The method for preparing a self-curing 3D printed magnesium oxychloride and calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (4), the magnesium-calcium composite solid phase component is added to the composite printing liquid obtained in step (2) at a solid-liquid ratio of 1.2 g / mL to obtain composite bone cement printing slurry.

5. The method for preparing a self-curing 3D printed magnesium oxychloride calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (5), the printing parameters include printing path, number of printing layers, line spacing, layer height, nozzle diameter, and extrusion speed.

6. The method for preparing a self-curing 3D printed magnesium oxychloride calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (5), the three-dimensional structure includes cylindrical, cuboid, grid-like, and irregular scaffold structures that match the morphology of bone defects.

7. The method for preparing a self-curing 3D printed magnesium oxychloride and calcium sulfate composite bone cement scaffold according to claim 1, characterized in that, In step (6), allow the mixture to stand and cure for 60-480 minutes.

8. A magnesium oxychloride calcium sulfate composite bone cement scaffold prepared by any one of claims 1-7.

9. The magnesium oxychloride calcium sulfate composite bone cement scaffold according to claim 8, characterized in that, The porosity of the magnesium oxychloride calcium sulfate composite bone cement scaffold is 20% to 60%, and the compressive strength is 30 to 70 MPa.

10. The application of the magnesium oxychloride calcium sulfate composite bone cement scaffold according to claim 9 in the preparation of bone defect repair materials.

Citation Information

Patent Citations

  • Modified magnesium oxychloride cement products and their preparation methods

    CN102285785A

  • Fiber-reinforced inorganic slurry composite material and preparation method thereof

    CN102367208A